Black Soldier Fly (Hermetia illucens) Oil Inclusion and its Effects on Growth Performances in Common Carp (Cyprinus carpio) - Vivi Endar Herawati; Heni Tri Jayanti; Tita Elfitasari; Sapto Purnomo Putro; Seto Windarto (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research